Molecular identification of zoonotic taeniids metacestodes in several rodent species trapped in Central Europe - Husák, Tomáš; Čadková, Zuzana; Máca, Ondřej; Kouba, Marek; Klimková, Zdeňka; Sehnal, Richard; Nápravníková, Jana; Hrabětová, Václava; Jankovská, Ivana; Vadlejch, Jaroslav; Langrová, Iva (Frontiers in Veterinary Science, 2025)
BackgroundLarval stages of carnivore cestodes in rodents have been extensively studied for decades, primarily based on morphological indicators. Numerous datasets, particularly from Central Europe, exist on this topic. Traditionally, the shape, number, and size of hooks have been key distinguishing features. However, recent findings suggest that morphology alone may not provide accurate identification. In this study, rodent livers from various habitats across five regions of the Czech Republic were examined for the presence of taeniid larval cestodes.MethodsA total of 2,934 rodent specimens were collected using snap traps between 2014 and 2022. Taeniid metacestodes detected in these intermediate hosts were subsequently subjected to species determination through molecular (targeting the cytochrome oxidase subunit I gene) and morphological examinations.ResultsThe following cestodes were identified using molecular methods: Hydatigera kamiyai (found in Apodemus flavicollis, Apodemus sylvaticus, Microtus arvalis, and Microtus agrestis), Taenia martis (in A. flavicollis, M. arvalis, and Myodes glareolus), and Versteria mustelae (in M. arvalis and My. glareolus). Sequencing of 55 PCR-positive isolates revealed 13 haplotypes of H. kamiyai, one of T. martis and four of V. mustelae. Further, we also identified co-infection by more metacestode species or haplotypes. No rodent liver samples tested were positive for Echinococcus multilocularis or Hydatigera taeniaeformis sensu stricto, either through morphological or molecular identification methods. Furthermore, no other cryptic species were detected during this study.ConclusionThis study presents the first comprehensive molecular data on the aforementioned zoonotic cestode species in the Czech Republic. The findings demonstrate the importance of using molecular techniques for Taeniidae species determination, as morphological methods may lead to erroneous classifications. Furthermore, this research highlights the importance of accurate diagnostic techniques, enabling the development of effective prevention and control strategies by verifying host–parasite relationships.